ANALISIS PEMANFAATAN FUNGSI ATM TERHADAP PENINGKATAN PELAYANAN NASABAH PADA PT. BCA TBK MEDAN - Lidia Yunita (Jurnal Mantik Penusa, 2016)
The banking sector is now very advanced with the development of science and technology human beings. Human life is very mobile, it must demand a lifestyle that is practical and fast. BCA Bank is a private bank that is considered quite good, because it is the biggest and most reliable transactional bank in Indonesia. In general, the function ATM that is to make transactions of cash withdrawal as: to withdraw cash 24 hours a day, the customer does not depend on the hours of service of the bank, can be used as a debit card, free long queues, save time, because it no longer follow administrative procedures, more easily achieved because it is available in various strategic locationsBased on the research that has been done, the problems faced by PT. BCA Tbk is sebgai follows: "How far Utilization Of Function ATM Customer Service Improvement".The hypothesis is a temporary answer to the problems faced and be verifiable through analysis and evaluasi.Hipotesa dikemukan in connection with the issue is: "the level of use of the ATM facility at PT. BCA is still low, causing queues at the teller. "Data analysis was done by observation (observation) and interviews conducted by researchers with the authorities.Based on research done next, we can conclude the extent of use of ATM functions to the improvement of customer service are: ATM is a machine or device that serves as a bank service automatically, unable to withdraw money transfer and other bill payments. ATM as one of the bank's efforts to improve services to customers to more efficiently and effectively by optimizing communication network, so as to increase revenue and reduce queues at teller. ATM service transactions such as cash withdrawal and balance print an act ivity that is most widely used by customers of Bank BCA.